2016
DOI: 10.1186/s12876-016-0555-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoking influences the need for surgery in patients with the inflammatory bowel diseases: a systematic review and meta-analysis incorporating disease duration

Abstract: Background: Studies examining the association between smoking and the need for surgery in patients with Crohn's disease and ulcerative colitis have reached inconsistent conclusions. These studies often do not differentiate between patients undergoing early surgery and patients having surgery later in their disease course. Our study examined the association between smoking status and time to first bowel resection in patients with Crohn's disease and ulcerative colitis. Methods: We searched MEDLINE and EMBASE fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 31 publications
1
32
2
2
Order By: Relevance
“…Many Western studies found current smoking to increase the risk and exacerbate the disease course of CD and to have the opposite impacts on UC [18, 21, 33]. However, we did not find statistically significant association between smoking and disease outcomes of CD and UC in the USA cases.…”
Section: Discussioncontrasting
confidence: 90%
“…Many Western studies found current smoking to increase the risk and exacerbate the disease course of CD and to have the opposite impacts on UC [18, 21, 33]. However, we did not find statistically significant association between smoking and disease outcomes of CD and UC in the USA cases.…”
Section: Discussioncontrasting
confidence: 90%
“…A recent systematic review and meta-analysis conducted in Canada demonstrated that the time from diagnosis to surgery was shorter in smokers until a primary intestinal resection due to CD. 13 Our study did not observe such a link, probably owing to the reduced number of smokers in our sample (only 11 from the 123 patients analyzed), cultural trend in our country, and intense campaigns and public health efforts against smoking.…”
Section: Discussioncontrasting
confidence: 58%
“… 11 12 Other factors, such as smoking, can also influence the timing of the need for a surgical resection. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Poor communication included insufficient discussion about fundamental aspects of patients’ care within 3 months of diagnosis, including characteristics of IBD (24.4%), treatment goals (27.4%), or risks-benefits of treatment (40.5%). Half the patients with CD (50.6%) could not recall being told about the importance of avoiding smoking, despite well-established risks associated with smoking and exacerbation of CD [ 25 , 26 ]. For patients with established disease, communication deficits in the preceding 12 months included insufficient discussion of the goals of treatment (48.1%), general lifestyle issues (44.8%), medical treatment options (16.2%), or current symptoms (11.8%).…”
Section: Discussionmentioning
confidence: 99%